ANALISIS PENDAPATAN ASLI DAERAH PROVINSI JAWA BARAT DENGAN PENERAPAN ERROR CORRECTION MODEL - Yulistiani Eka Pratiwi; Dinar Melani Hutajulu (Jurnal Ekonomi dan Bisnis, 2022)
The implementation of regional autonomy in Indonesia provides flexibility for each region to manage regional potential in accordance with regional regulations based on legislation. Some regional revenues, namely Regional Original Income sourced from taxes, levies and the results of wealth management are separated from other legitimate income. Regional Original Income (PAD) is one of the criteria used to measure and evaluate the success of regional autonomy and independence. The independence of West Java Province can be seen from the ratio of independence which is measured by the comparison between local revenue and regional transfers. The independence ratio shows that West Java Province is still supported by transfer funds from the central government to finance regional expenditures. The purpose of this study is to examine the variables that affect the PAD of West Java Province. The independent variables used are population, government spending, PMDN and PMA. While the dependent variable is PAD. The data used is secondary data in the form of time series from 1990-2021 which is contained in the publications of the Central Statistics Agency. The estimation model used is the Error Correction Model (ECM) approach. The results of data processing show that in the long term population, government spending, PMDN and PMA affect PAD. Meanwhile, in the short term, only the PMDN variable has an impact on PAD.